Scaffold based on castor oil as an osteoconductive matrix in bone repair: biocompatibility analysis - Lima, Fabianne Soares (2022)
To analyze the biocompatibility of the scaffold produced from a natural polymer derived from castor oil through hemolytic activity and antimicrobial activity, to enable the clinical application. Three in vitro tests were performed: Hemolytic activity test - Polymer partially dissolved in contact with blood agar; Hemolytic activity test in sheep's blood - Polymer extract with red blood cells solution; Antimicrobial activity test - Solid polymer in direct contact with E. Coli and S. Aureus. For hemolytic tests, none of the samples showed hemolysis. Negative hemolytic activity is a good indicator, as the maintenance of the blood clot in the area of the lesion is essential for the formation of new tissue. For the antimicrobial activity test, no significant activity was observed against the bacteria used. The polymer is not toxic to red blood cells, being viable for clinical application as a matrix for tissue regeneration.